Photoluminescence of Tetra(benzimidazole)phenylethene Derivatives and Their Carbene Metallacycles in Aggregates and Langmuir-Blodgett Films - Wang, Chao-Yu (Langmuir : the ACS journal of surfaces and colloids, 2024)
Molecular structure, external stimuli, and environmental factors all have a strong effect on the internal molecular rotation and vibration of aggregate-induced emission (AIE) luminogens. Here, we report the AIE effect for several newly synthesized amphiphilic tetra(benzimidazole)phenylethene (TBiPE) derivatives and their binuclear N-heterocyclic carbene silver (NHC-Ag) metallacycles in solutions, aggregates, and Langmuir-Blodgett (LB) films. Monolayer behaviors and microscopic images indicate that introducing alkyl chains and binuclear NHC-Ag metallacycles can facilitate the formation of a well-defined insoluble monomolecular layer at the air-water interface. Absorption and luminescence spectral features suggest that both the TBiPEs' cyclization structure and binuclear NHC-Ag metallacycles can provide additional driving forces to restrict the internal molecular motion of the tetraphenylethene (TPE) unit, thus enhancing the AIE effects. Further, external stimuli and environmental factors such as poor solvent addition and LB film deposition also play important roles in the photoluminescent intensity, maximum wavelength, and lifetime. These internal and external factors can result in around 30-40 nm blue-shift for the maximum luminescence wavelength and 2-3 times shorter for the luminescent lifetime. These phenomena can be attributed to the reason that the nonradiative energy transfer efficiency is weakened because of the enhanced hydrophobic interaction and metal-carbene coordination as well as the closely packed arrangement of AIEgens in the LB films; consequently, the radiation energy transfer efficiency increased